Determinación del costo de los platos fuertes que oferta el departamento de alimentos y bebidas de la Compañía Hoteles y Servicios Almendral Cía. Ltda. de la ciudad de Loja, mayo 2014 - Manotoa Alvarado, Wilson Freddy (2015)
The development of the theme "DETERMINATION OF COST OF DISHES THAT OFFER THE DEPARTMENT OF FOOD & BEVERAGE COMPANY ALMENDRAL HOTELS AND SERVICES CIA. LTDA. LOJA CITY, MAY 2014 "is intended to defray costs and check the highlights Filet Mignone, Albardado Salmon with prosciutto, lojana Cecina, three peppers Steak and Corvina sea fruit, occurring in the Howard Johnson Hotel Loja, to contribute to the improvement of the activities of the same In compliance with the goals the unit cost in each process was determined and therefore the finished product for compliance costing the standard recipe was developed by defining the products involved. Raw material, hand labor and indirect production costs: an initial inventory, a chart of accounts, accounting records and documents that facilitated the control of cost elements used are then developed. Finally it is concluded that the application of the accounting process cost the company Almendral hotels and services, it was determined the cost of products based on the design and format of Request for raw materials. Manpower according to the working hour was calculated and applied to the time it takes each dish occur Similarly it can be recommended to the masters of the company Hoteles y Servicios Almendral control recommendations in carrying out fortnightly inventories. Be aware of the updating of product prices